An interprofessional model to improve LGBTQ+ specific cultural competence in dental and pharmacy students - Anubhuti Shukla; Sriha Yalamanchi; Guillermo Tamayo-Cabeza; Amanda Albright; Zachary A. Weber; April D. Newton (PLoS ONE, 2025)
Background Disproportionate access to healthcare services among the Lesbian, Gay, Bisexual, Transgender, Queer or Questioning and others (LGBTQ+) population can be partially attributed to the lack of cultural competence among healthcare providers. The aim of this study was to evaluate the impact of an interprofessional model in improving cultural competence and clinical preparedness among dental and pharmacy students for providing LGBTQ+ specific care. Methodology This study is a retrospective observational study which used a novel interprofessional model of three different LGBTQ+ focused educational interventions within a group of dental and pharmacy students. The study used pre- and post-surveys, Assessment of Interprofessional Team Collaboration Scale (AITCS-II) and the Team Observed Structured Clinical Encounter (TOSCE) evaluations to assess the effectiveness of the interventions. Descriptive statistics, Fisher’s exact test, Wilcoxon signed-rank test, Welch test, Kruskal-Wallis Test, and pairwise Wilcox Test were employed to analyze quantitative data while qualitative insights were gathered from evaluator comments and student feedback. Results The study evaluated cultural competence among 154 dental and pharmacy students revealing improved cultural humility post-intervention, particularly for dental students although not statistically significant (p>0.05). Students participating in multiple interventions had higher mean scores, but the differences were not significant (p>0.05). Significant differences were found among interprofessional teams of students in the domains of roles and responsibilities (p = 0.039) and patient centered approach (p = 0.039). No significant differences were found in individual scores participation in the teams (p = 0.018). Students also provided positive feedback on the program’s impact on their understanding of LGBTQ+ health issues and inclusive care. Conclusion This program was a novel intervention aimed at improving cultural competence for health professional students in an interprofessional environment Further research in the direction can be useful in creating replicable programs.